Posterior reversible encephalopathy syndrome associated with use of anlotinib to treat squamous cell carcinoma of the cervix: case report and literature review - Lin, Jietao; Chen, Wenmin; Zhong, Sha; Qian, Kai; Chen, Hanrui; Lin, Lizhu (Frontiers in Pharmacology, 2023)
Posterior reversible encephalopathy syndrome (PRES), a neurological disorder with an unknown aetiology, is characterised by visual impairment, headache, vomiting, seizures, and transient alterations in consciousness.We present the case of a 49-year-old woman with advanced cervical carcinoma who received second-line therapy with oral anlotinib (12 mg, days 1-14, every 21 days) and injectable tislelizumab (200 mg, day 1, every 21 days).After 7 days of anlotinib administration, she began experiencing symptoms suggestive of PRES and was diagnosed on day 11. Interruption of anlotinib and supportive treatment led to the recovery of her binocular vision. The Naranjo score (+5) graded the causality of this reaction as probable, suggesting the possibility that the event may have been an adverse reaction to anlotinib.